AGE AS A RISK FACTOR FOR CARDIOVASCULAR EVENTS IN PATIENTS WITH HYPERTENSIVE CRISES AFTER 12-MONTH FOLLOW-UP: A GREEK REGISTRY. (June 2022) - Fragkoulis, Christos; Polyzos, Dimitrios; Mavroudis, Andreas; Dimitriadis, Kyriakos; Kariori, Maria; Leontsinis, Ioannis; Andrikou, Ioannis; Kakouri, Niki; Kouremeti, Maria; Grigoriou, Kalliopi; Thomopoulos, Costas; Konstantinidis, Dimitrios; et al.
Abstract : Objective: Few data have been published regarding the long-term prognosis of patients with hypertensive crises (HC). The aim of our study was to record the prevalence and clinical phenotype of patients with hypertensive urgencies (HU) and emergencies (HE) assessed in the emergency department (ED) and during ospitalisation and a 12-month follow-up to record new events in a Greek tertiary hospital. Design and method: The registry population consisted of patients admitted to the ED with acute increase in blood pressure (BP) (systolic BP> or = 180mmHg and/or diastolic BP > or = 120mmHg) and depending on the presence or absence of acute hypertension-mediated target organ damage they were divided into the HE and the HU group, respectively. In all patients the demographic and clinical parameters were recorded for 12 months and there was a 12-month follow-up for new end points. Results: Out of 38, 589 patients assessed in the ED during a period of 12 months, 353(0.91%) had HC, out of whom 256(72.5%) had HU and 97(27.5%) had HE. The mean age of all patients was 67.4 ± 12.9 years, 49% were males and 80% had a history of hypertension. During the study period 81 patients were excluded for not completing the follow-up. We stratified the total population of HC by age separating patients into two groups, e.g. > or = 65 and < 65 years old, and ospital the composite end point consisting of deaths or ospitalisations caused by cardiovascular disease. Patients > or = 65years old presented more composite events (36 vs 8 events, p = 0.019, HR for patients > or = 65years 2.68, 95% CI 1.18–6.12). Cox regression models were adjusted for age, gender, cardiovascular disease, chronic kidney disease and diabetes mellitus. Conclusions: Our study implies that age > or = 65years is an independent risk factor for deaths or ospitalisations caused by cardiovascular disease in patients with HC. There is an arising necessity for more intensive follow-up of these patients and the need for further research in this setting.